Functional Microbiomics in Liver Transplantation: Identifying Novel Targets for Improving Allograft Outcomes. Issue 4 (April 2019) - Kriss, Michael; Verna, Elizabeth C.; Rosen, Hugo R.; Lozupone, Catherine A.
Abstract : Gut dysbiosis, defined as a maladaptive gut microbial imbalance, has been demonstrated in patients with end-stage liver disease, defined as a contributor to disease progression, and associated clinically with severity of disease and liver-related morbidity and mortality. Despite this well-recognized phenomena in patients with end-stage liver disease, the impact of gut dysbiosis and its rate of recovery following liver transplantation (LT) remains incompletely understood. The mechanisms by which alterations in the gut microbiota impact allograft metabolism and immunity, both directly and indirectly, are multifactorial and reflect the complexity of the gut-liver axis. Importantly, while research has largely focused on quantitative and qualitative changes in gut microbial composition, changes in microbial functionality (in the presence or absence of compositional changes) are of critical importance. Therefore, to translate functional microbiomics into clinical practice, one must understand not only the compositional but also the functional changes associated with gut dysbiosis and its resolution post-LT. In this review, we will summarize critical advances in functional microbiomics in LT recipients as they apply to immune-mediated allograft injury, posttransplant complications, and disease recurrence, while highlighting potential areas for microbial-based therapeutics in LT recipients.